Substrate and fertigation doses on acclimatization of micropropagated Agave americana var. oaxacensis plants - Enríquez del Valle, José Raymundo; Estrada Silias, Anabey; Rodríguez Ortíz, Gerardo; Velasco Velasco, Vicente Arturo; Campos Ángeles, Gisela Virginia (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
In order to ensure adaptation in the greenhouse of Agave americana var. oaxacensis plants obtained in vitro, the effect of media and fertigation dose on acclimatization and growth of 180 plants were evaluated. This work was conducted in a greenhouse at the Instituto Tecnológico del Valle de Oaxaca, Mexico, in early 2012. Plants were fresh from the laboratory. The experiment was established according to completely randomized design and factorial arrangement with 2 (substrates: sand and perlite) x 5 (fertilization: 1, 25, 50, 75 and 100%). The experimental unit was a plant in a plastic container of 150 cm3 with 18 replications. Fertilization was based on the universal Steiner's solution, and daily, each plant received 10 mL at substrate level for 12 weeks. Growth was evaluated in leaves, stems and roots, performing analysis of variance and Tukey's test (α = 0.05). All plants were adapted, but those plants which grew in perlite achieved the best growth on leaf area, root volume, total fresh weight and root dry matter and total biomass. The size of the plants at the end of the acclimatization stage was related to the amount of nutriments in the nutrient solution.